2014
DOI: 10.1002/adma.201401692
|View full text |Cite
|
Sign up to set email alerts
|

Closely Interconnected Network of Molybdenum Phosphide Nanoparticles: A Highly Efficient Electrocatalyst for Generating Hydrogen from Water

Abstract: A closely interconnected network of MoP nanoparticles (MoP-CA2) with rich nano-pores, large specific surface area, and high conductivity can function as a highly active non-noble metal catalyst for electrochemically generating hydrogen from acidic water. The network exhibits nearly 100% Faradaic efficiency and needs overpotentials of 125 and 200 mV to attain current densities of 10 and 100 mA cm(-2) , respectively. The catalytic activity is maintained for at least 24 h.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
504
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 804 publications
(524 citation statements)
references
References 55 publications
18
504
1
1
Order By: Relevance
“…S9) shows that the hexagonal phase Mo 2 C nanowires can be obtained. This is in accordance with the previous reports [24,25]. These results suggest that the structure and morphology of the final sample have a close relationship with the pretreatment of calcination and annealing atmosphere.…”
Section: Science China Materialssupporting
confidence: 82%
See 1 more Smart Citation
“…S9) shows that the hexagonal phase Mo 2 C nanowires can be obtained. This is in accordance with the previous reports [24,25]. These results suggest that the structure and morphology of the final sample have a close relationship with the pretreatment of calcination and annealing atmosphere.…”
Section: Science China Materialssupporting
confidence: 82%
“…It is generally acknowledged that three principle steps for the conversion of H + to H 2 have been suggested for the HER in acidic media as below [24] The linear portions of the Tafel plots (Fig. 5b) were fit to the Tafel equation (η = blogj + a, where b is the Tafel slope) [44,45].…”
Section: Science China Materialsmentioning
confidence: 99%
“…The other X-ray diffraction peaks at 34.4, 37.9, 39.6, 61.6 and 74.6°are attributed to the diffractions of the (100), (002), (101), (110) and (112) faces, respectively, of hexagonal Mo 2 C (JCPDS 35-0708) (Supplementary Figure S3). It is found that the carbon peak is substantially reduced when the concentrations of (NH 4 ) 6 Figure S4a), probably because optimization of the chemical compositions and microstructure could be realized at this concentration. 18,19 Furthermore, the variation tendency of the R ct determined from the semicircle registered at low frequencies (high Z') was highly consistent with the polarization curves (Supplementary Figure S4b), indicating that the samples prepared in 2.5 mM (NH 4 ) 6 Mo 7 O 24 solution create the fastest electrode kinetics.…”
Section: Theoretical Modelsmentioning
confidence: 99%
“…1 Remarkable advances have been made recently regarding the use of transition metal dichalcogenides, phosphides, carbides, nitrides and borides as promising non-noble-metal catalysts for HER. 1,2,[4][5][6][7] Among these non-noble-metal HER catalysts, molybdenum carbide (Mo 2 C), which features a d-band electronic structure and catalytic properties similar to those of platinum, has been demonstrated as an active and stable HER catalyst, even in the form of bulky particles. [8][9][10][11][12][13] Previous research has revealed that the coupling of Mo 2 C particles with nanocarbons is an excellent strategy for improving the HER activity, 8,9,[14][15][16] because of the following reasons: (1) carbon supports create a resistanceless path for rapid electron transfer and also effectively inhibit Mo 2 C nanoparticle aggregation; (2) coupling conjugation can downshift the d-band center of molybdenum by inducing a charge transfer from molybdenum to carbon, thus achieving a relatively moderate Mo-H bond strength for enhanced H desorption.…”
Section: Introductionmentioning
confidence: 99%
“…However, the high price and scarcity of the noble metal have critically impeded the large-scale application for hydrogen energy [7]. Thus it still remains a challenge to develop highly active HER catalysts based on materials that are more abundant at lower cost [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%